Development of a component for the acceptance of informed consent to share production data - Nuñez Jimenez, Daniel; Garcia, David (International Food Policy Research Institute, 2024)
This report describes the process carried out for the development of a component in the e-Agrology mobile application, which allows the farmer to accept informed consent, thus authorizing the sharing of data on their agricultural production.